Study on the Therapeutic Mechanism of Lumbar Disc Herniation Treated by Sling and Massage Exercise Technique - LI Li; Qin WANG; Ziyun FENG; Jinglong SUN; Haifeng LU (康复学报)
Objective:To explore the clinical effect and therapeutic mechanism of sling and massage exercise technique on lumbar disc herniation(LDH)based on musculoskeletal ultrasonography(MSUS)and surface electromyography.Methods:A total of 236 LDH patients were collected. The eligible patients were divided into massage treatment group(group A), sling exercise therapy group(group B), and sling and massage exercise technique group(group C), and routine treatment group(group D)by random number table method, with 59 cases in each group. All the above groups were treated for 4 weeks. Japanese Orthopaedic Association(JOA)scores, visual analogue score(VAS), the changes in thickness of local core stable muscles, the mean power frequency(MPF)and the integrate electromyogram(IEGM)were used to evaluate the clinical efficacy before treatment and after four weeks'treatment.Results:The effective rate of group C was higher than that of the other three groups(P<0.05). After four weeks'treatment, VAS scores were all decreased(P<0.05), and group C were better than the other three groups(P<0.05)respectively. After four weeks'treatment, the JOA scores of the four groups were all higher than those before treatment(P<0.05), and group C was superior to the other three groups(P<0.05). The thickness of the back muscle, MPF, IEGM of group B and C after treatment were all higher than before. Group C was higher than group B(P<0.05). There was no significant difference before and after treatment in group A and D(P>0.05).Conclusion:Sling and tuina exercise technique has better effect in relieving pain and improving lumbar motion. This may be related to the increasing thickness of lumbar dorsal muscle and core muscle group, and enhancing muscle endurance and muscle strength of lumbar dorsal muscle for changing the muscle histology and electrophysiology.